Urbanización de la sociedad agraria vasca: el caserío del periurbano de San Sebastián - Alberdi Collantes, Juan Cruz (Geographicalia, 2016)
In this paper we investigate the last changes in and the space implications that they are challenging, taking to account the analysis of some elements of the rural basque society. So, we direct our investigation to the study of the distribution of the family heritage (mayorazgo), because the basque rural society is organised around it. In that moment, the mayorazgo institution is leaving his function and the family heritage is splitting among the brothers. As consequence, the farm production is left because the new farms don’t have enough flour. The village, the second social space after the family house, is leaving change by the family relations. So, the rural basque society, in that moment, is directed by the urban society near it.